1982
DOI: 10.1029/rs017i003p00599
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation with distance and wind speed of HF surface waves over the ocean

Abstract: An HF monostatic experiment is performed in order to evaluate the relative attenuation with distance of radio waves propagating in the ground wave mode over the sea surface, at 7 and 14 MHz. Clear evidence of the wind speed (causing the sea roughness) influence arises from the data, particularly at 14 MHz. The results are compared to Barrick's theoretical calculations, and a good agreement is found for the values of attenuation rates (in decibels per kilometer) and their variation with the wind speed in the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
2
5
1
Order By: Relevance
“…A loss of radar coverage was also noticed during strong winds, especially during the Mistral wind regime. This is consistent with the fact that propagation losses in HF ground wave propagation mode increase with sea state, leading to a decrease of the radar range, as shown both theoretically (Barrick 1971) and experimentally (Forget et al 1982). …”
Section: Setup Of the Hf Radar Systemsupporting
confidence: 87%
“…A loss of radar coverage was also noticed during strong winds, especially during the Mistral wind regime. This is consistent with the fact that propagation losses in HF ground wave propagation mode increase with sea state, leading to a decrease of the radar range, as shown both theoretically (Barrick 1971) and experimentally (Forget et al 1982). …”
Section: Setup Of the Hf Radar Systemsupporting
confidence: 87%
“…Recent, careful analyses of experimental radar data [Forget et al, 1982] at 7 and 14 MHz have shown that propagation loss at these frequencies follows the theoretical results of Barrick [1971a, b] closely, indicating a clear dependence on sea state. Our experience at 25 MHz also shows pronounced sea state 320 LYONS AND BARRICK: ATTENUATION OF COASTAL RADAR SIGNALS effects: in higher seas, maximum range is decreased.…”
Section: Introductionsupporting
confidence: 60%
“…Our experience at 25 MHz also shows pronounced sea state 320 LYONS AND BARRICK: ATTENUATION OF COASTAL RADAR SIGNALS effects: in higher seas, maximum range is decreased. Forget et al [1982] found that measured attenuation rates were slightly greater than theory predicted. Unpublished measurements of one-way path loss over the ocean off the coast of Maine (taken on many frequencies from 3 to 30 MHz 15 years ago by the second author) also show close agreement with theoretical values at frequencies below about 20 MHz, but a consistent trend toward lower losses than predicted above 20 MHz.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, sea state influences propagation of the EM wave (cf. Barrick 1971a, b;Forget et al 1982). Range increases with increasing sea state due to a stronger backscatter signal but at the same time attenuation increases due to loss of power by stronger backscatter at shorter ranges.…”
Section: Range Dependencymentioning
confidence: 96%
“…Note that WAM is estimating the processes at the ocean surface and does not incorporate EM scattering processes which, especially at high HF frequencies (28 MHz), will result in an additional decrease of first-order backscatter power with increasing wind speed (cf. Barrick 1971a, b;Forget et al 1982).…”
Section: Wind Speed and Bragg Frequencymentioning
confidence: 98%